EDUKASI KEBUTUHAN GIZI REMAJA PUTRI - Irni Setyawati; Kusniyati Utami; Dian Soekmawaty Riezqy Ariendha; Hardaniyati Hardaniyati; Yesvi Zulfiana; Sarah Husniyati (Stikes Yarsi Mataram, 2022)
The quality of the nation's next generation is largely determined by young women who act as prospective mothers. Data from the Riskesdas report for the NTB province in 2018 reported that the city of Mataram had the second most thin women aged >18 years (14.02%) after North Lombok district, which was 15.99%. An initial survey conducted on 20 female students by accident at STIKes Yarsi Mataram in February 2021 found 30% of female students had Lila <23.5 cm and deliberately limited eating because they did not want to look fat. This situation shows that not all female students at STIKes Yarsi Mataram have good nutritional status and awareness of their nutritional needs. Based on the problems above, community service